Monetary mechanics: A financial view - Éric Tymoigne (Levy Economics Institute of Bard College, 2014)
This paper develops the framework of analysis of monetary systems put together by authors such as Macleod, Keynes, Innes, and Knapp. This framework does not focus on the functions performed by an object but rather on its financial characteristics. Anything issued by anybody can be a monetary instrument and any type of material can be used to make a monetary instrument, as these are unimportant determinants of what a monetary instrument is. What matters is the existence of specific financial characteristics. These characteristics lead to a stable nominal value (parity) in the proper financial environment. This framework of analysis leads the researcher to study how the fair value of a monetary instrument changes and how that change differs from changes in the value of the unit of account. It also provides a road map to understanding monetary history and why monetary instruments are held.
Keywords: E5; E42; E44; 330; Monetary Instrument; Money; Fair Value; Unit of Account